Effects of Obligate Heterofermentative Lactic Acid Bacteria Alone or in Combination on the Conservation of Sugarcane Silage - Gomes, Ana Luiza Mendonça; Bueno, Antônio Vinicius Iank; Osmari, Milene Puntel; Machado, Juliana; Nussio, Luiz Gustavo; Jobim, Clóves Cabreira; Daniel, João Luiz Pratti (Frontiers in Microbiology, 2021)
Our objective was to determine the effects of two strains of obligate heterofermentative bacteria, alone or in combination, on the fermentation profile, gas production kinetics, chemical composition, and aerobic stability of sugarcane silage. A plot of sugarcane was manually harvested, mechanically chopped and treated with: distilled water (5 mL kg-1; Control), Lentilactobacillus hilgardii CNCM I-4785 [3 × 105 colony-forming units (cfu) g-1; LH], Lentilactobacillus buchneri NCIMB 40788 (3 × 105 cfu g-1; LB), and LH+LB (1.5 × 105 cfu g-1 of each strain). Treated forages were packed into 1.96-L gas-tight silos (0.40 porosity) and stored at 25 ± 1.5°C for 70 d (4 replicates per treatment). All heterolactic inoculants were effective to increase acetic acid concentration and inhibit yeast metabolism, as treated silages had lower formation of ethanol, ethyl esters and gas during fermentation. Lower fungal development spared soluble carbohydrates, consequently resulting in silages with higher in vitro digestibility. Nevertheless, L. buchneri was the most effective strain to extend the aerobic stability of sugarcane silage (based on both temperature and pH rise). The use of L. buchneri alone or in combination with L. hilgardii, applied at 3 × 105 cfu g-1, is a feasible strategy to inhibit yeast metabolism and increase the nutritional quality of sugarcane silage.